Mechanical Properties of ST 37 Manufactured by Gas Tungsten Arc Welding using Cannibal Consumable Manufacturing Filler - Saragih, Albert Daniel; Riswanda; Prasetyo; Nugraha, Syahrul Dwi; Al-Qashtalani, Tb. Moch Mario (Piston: Journal of Technical Engineering, 2025)
In this paper, the macrostructure and mechanical properties of medium carbon steel with cannibal consumable filler by using the GTAW process have been investigated. The medium carbon steel (ST 37) plates with dimensions of 300 × 250 ×3 mm were used for welding and 2.5 mm of thickness for the filler. For welding parameters, current of 80 A was chosen and observed over the welded specimen. Welding was performed with single Vgroove butt Joint design, 30° bevel angle. Preparation of samples was done according to standard. To explore the optimum welding specimen, both tensile and bending tests were carried out. The result of the welding process with the current of 80A shows that the face part tends to be more embossed and the root part looks less embossed, there are parts that lack penetration. This causes a lack of weld strength due to incomplete penetration of the root part. The face section produces maximum and strong results, while at the root there are cracks that are almost broken. This is due to lack of fusion because the current is too small resulting in differences in weld strength between the face and root, which affects the bending test results. In the tensile test results, a fracture occurred in the weld metal in the form of a brittle fracture. This is caused by a lack of fusion and very minimal penetration of the filler metal into the weld groove. Based on the macro test analysis carried out, minimal root penetration or no penetration occurs, while the weld seam accumulates on the face. Based upon the present study it is not recommended that 80 A of welding current when GTAW process using canibal consumable filler. The current of 80A may need to improve to produce good welding.